Hubungan Asupan Energi, Preferensi Makan, Pengaruh Teman Sebaya, dan Pendidikan Orang Tua dengan Kejadian Gizi Lebih Remaja di Depok: Hubungan Asupan Energi, Preferensi Makan, Pengaruh Teman Sebaya, dan Pendidikan Orang Tua dengan Kejadian Gizi Lebih Remaja di Depok - Nurbaiti, Krisanti; Marjan, Avliya Quratul; Maryusman, Taufik; Octaria, Yessi Crosita (Amerta Nutrition, 2023)
Background: Overnutrition among Indonesian teenagers is a nutritional problem that has increased in recent years from 7.3% to 13.5%. Factors that contribute in the improvement of nutritional status include diet, lifestyle, and socio-economics. Overnutrition can lead to health complications, including non-communicable diseases. Objectives: To identify the relationship between energy intake, food preferences, peer influence, and parental education with the incidence of overnutrition among teenagers in Depok. Methods: This study used an observational approach with a cross-sectional design. The sample was taken by stratified random sampling from a chosen Senior High School (SMA) in Depok with a total of 108 participants. Nutritional status was obtained by measuring body weight (BB) and height (TB) using BMI-for-age (BMI/U), energy intake was measured by interviewing the 2x24-hour food recall, food preferences used the food and beverage preference questionnaire (FBPQ), peered influence was measured using the peered influence scale (PIS), and parental education was gathered through a questionnaire. Relationship analysis was carried out by chi-square and Fisher's exact tests. Results: Bivariate analysis shows that energy intake (p=0.030), food preferences (p=0.019), and peer influence (p=0. 006) were associated with the incidence of overnutrition. Parental education (father, p=0.365; mother, p=0.103) were not significantly associated with the incidence of overnutrition.   Conclusions: Individual factors among teenagers showed a relationship with the incidence of overnutrition. Teenagers need to pay attention to their energy intake, develop healthy food preferences, and utilize peered influence to adopt good eating behaviours to prevent overnutrition.